2018
DOI: 10.3390/healthcare6020039
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted and Tailored eHealth Weight Loss Program for Young Women: The Be Positive Be Healthe Randomized Controlled Trial

Abstract: Young women are gaining weight rapidly. Evidence for effective weight loss interventions targeting young women is lacking. This randomized controlled trial assessed the efficacy and acceptability of a six-month targeted and tailored eHealth weight loss program for young women (Be Positive Be Healthe (BPBH)). Women aged 18–35 years were randomized to BPBH (n = 29) or control (n = 28). BPBH supported participants to modify diet and physical activity behaviours using evidenced-based strategies (e.g., self-monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 42 publications
1
87
0
2
Order By: Relevance
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 studies measured changed in BMI, with 32 of these using an objective measure for BMI, while four studies used self‐report measures for BMI . This includes the 20 studies from the meta‐analysis and a further 16 studies that reported BMI as an outcome, but results were not comparable and therefore not included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations